1993
DOI: 10.1161/01.hyp.21.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Reflex vasopressin and renin modulation by cardiac receptors in humans.

Abstract: Animal studies have shown that vasopressin secretion is modulated by arterial baroreceptors and cardiopulmonary volume receptors. Whether this is the case also in humans is controversial, however. To determine whether vasopressin is reflexly modulated by cardiac volume receptors, we studied the effect on plasma vasopressin (venous blood, radiolmmunoassay) of reducing venous return and left ventricular end-diastolic diameter (echocardiography) by producing a 20-minute lower body negative pressure in 14 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It has been reported in animals and in humans that secretion of AVP is modulated not only by changes in plasma osmolarity but also by changes in BV through baroreflex activation. We found a correlation betwee PV changes and AVP plasma levels that suggests the power of the volume in the modulation of the AVP secretion (15,26). Also, there was a correlation between AVP and urinary osmolality, which is the main factor that determines urine concentration to save water on the assumption of the upright posture.…”
mentioning
confidence: 61%
“…It has been reported in animals and in humans that secretion of AVP is modulated not only by changes in plasma osmolarity but also by changes in BV through baroreflex activation. We found a correlation betwee PV changes and AVP plasma levels that suggests the power of the volume in the modulation of the AVP secretion (15,26). Also, there was a correlation between AVP and urinary osmolality, which is the main factor that determines urine concentration to save water on the assumption of the upright posture.…”
mentioning
confidence: 61%
“…Vasopressin levels increased 3-fold in healthy subjects during HUT (21,22) and a similar increase was seen in patients with autonomic failure and falling blood pressure on HUT, but the increase was not sufficient compared with the magnitude of blood pressure fall (21). Studies have shown that the subnormal vasopressin response in patients with autonomic dysfunction is caused by a defect in the baroreflex arc (23,24).…”
Section: Neuroendocrine Changes and Orthostatic Hypotensionmentioning
confidence: 85%
“…A reduction in the adverse effect of Ang II on endothelial function may also explain the favorable effect of physical training, because physical training improves the sensitivity of cardiopulmonary reflexes, 21 which restrain renal secretion of renin. 22 Other factors are likely to play a role under this circumstance, however.…”
Section: Giannattasio Et Al Flow Mediate Dilatation In Heart Failurementioning
confidence: 99%